Boy soldier - McNab, Andy; Rigby, Robert (Corgi Children's London, 2006)
Danny Watts's grandfather, Fergus, was a traitor. He was arrested and left to rot and die in a Columbian jail. That's what Danny is told when his hopes of becoming a soldier are destroyed. But he knows something the army doesn't seem to know. Ages 12+